(untitled) (Communications in Computational Physics, 2010)
The characteristic of individual is described by the Penna model. Based on information entropy and the Penna model we define the entropy in the Penna model to discuss common ancestors and genetic diversity for two reproduction modes with and without mutation. About the problem of common ancestor, we find that all living individuals at any time step have a set of common ancestors which belongs to different times. They have the most recent common ancestor and earlier common ancestors. The analysis of genetic diversity shows that the complexity of ecosystems is caused by mutations and there is no contribution of sexual reproduction to conserving genetic diversity at long time scales. Moreover, in stable environment genetic diversity in asexual reproduction mode is higher than that in the sexual case.